Agreement and head movement : clitics, incorporation, and defective goals - Roberts, Ian G. (Linguistic inquiry monographs, 2010)
Here, Ian Roberts explores the consequences of Chomsky's conjecture that head-movement is not part of the narrow syntax the computational system that relates the lexicon to the interfaces.